2005
DOI: 10.1523/jneurosci.0098-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Channel Blockers Inhibit the Triggers of Attacks in the Calcium Channel Mouse Mutanttottering

Abstract: Humans with the disorder episodic ataxia type 2 (EA2) and the tottering mouse mutant exhibit episodic attacks induced by emotional and chemical stress. Both the human and mouse disorders result from mutations in CACNA1A, the gene encoding the ␣ 1 2.1 subunit of Ca v 2.1 voltage-gated calcium channels. These mutations predict reduced calcium currents, particularly in cerebellar Purkinje cells, where these channels are most abundant. 4-Aminopyridine (4-AP), a nonselective blocker of K v voltage-gated potassium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 35 publications
2
61
0
1
Order By: Relevance
“…A 45 min interval was used between injection and behavioral assessment or sacrifice and electrophysiological recordings to insure drug bioavailability. These dosages and delays were well tolerated and the most effective preventing dyskinesia attacks in tottering mice (Weisz et al, 2005). Chronic subcutaneous treatment was performed using 200 l Alzet miniosmotic pumps (model 2004; Durect Corporation) implanted subcutaneously in the back of the mice.…”
Section: Methodsmentioning
confidence: 99%
“…A 45 min interval was used between injection and behavioral assessment or sacrifice and electrophysiological recordings to insure drug bioavailability. These dosages and delays were well tolerated and the most effective preventing dyskinesia attacks in tottering mice (Weisz et al, 2005). Chronic subcutaneous treatment was performed using 200 l Alzet miniosmotic pumps (model 2004; Durect Corporation) implanted subcutaneously in the back of the mice.…”
Section: Methodsmentioning
confidence: 99%
“…46 Another study showed that aminopyridines (4-AP; 3,4-DAP) effectively prevent attacks in tottering mice. 47 The leaner mouse mutant also harbors a homozygous spontaneous mutation in the gene encoding the voltageactivated Ca 2ϩ channel ␣1A subunit, the pore-forming subunit of P/Q-type Ca 2ϩ channels. 48 On the basis of this mutation, an out-of-frame splicing event in the carboxy terminus occurs which results in dramatic reductions in P-type Ca 2ϩ channel function in cerebellar Purkinje neurons.…”
Section: Animal Models Of Episodic Ataxia Typementioning
confidence: 99%
“…These results suggest that the aminopyridines increase the threshold for attack initiation without mitigating the character of the attack. 47 From a clinical point of view, a prospective randomized controlled study is necessary to prove the short-and long-term effects of 4-AP and to compare them with ACTZ, which remains the standard treatment for EA 2.…”
Section: -Aminopyridinementioning
confidence: 99%
“…4,46,47 Several studies suggest that the truncated subunits exhibit dominant inheritance by exerting a dominant negative effect on the wild-type P/Q current activity. 44,48,49 SCA6 is a progressive ataxic disorder caused by a trinucleotide repeat (CAG) expansion in exon 47 of the CACNA1A gene. 2 This repeat is translated into a polyglutamine expansion in the distal C-terminus of certain splice variants of the P/Q-type calcium channel ␣1A subunit.…”
Section: Cacna1a Geneticsmentioning
confidence: 99%